PEMBUATAN SABUN CUCI PIRING RAMAH LINGKUNGAN KELURAHAN BESAR, KEC. MEDAN LABUHAN KOTA MEDAN - Luthfi Parinduri; Saypul Bahri; Cahya Putra Wibowo; Muhammad Age Rianto; Muhammad Fahreza; Rizki Wijaya Sirait; Aulia Maya Fahira Lubis; Fachrun Fikriyyah; Khairani Nasution; Sakinah Eprilia; Andi Syahputra; Kelana Sultan; M. Ikhsan Harahap; Intan Syahdila Febriandini (Jurnal Pengabdian Mitra Masyarakat, 2022)
KKNT activities are carried out as one of the tasks of students in implementing the Tri Dharma of Higher Education, namely community service. In accordance with the goals of higher education as stated in government regulation number 60 of 1999 concerning the Implementation of Higher Education (Chapter III article 3 paragraph 4) which reads Service to the Community as an Activity to Utilize Science in an Effort to Contribute to the Advancement of Society. From all the ingredients used in the manufacture of dish soap, about 20 liters of ready-to-use products are produced, with good quality. Physical appearance and washing results give results as well as products on the market. The product is then packaged in 50 bottles of 120 ml bottles. The liquid soap products, apart from being given to the participants of the training, are also distributed free of charge to the community in III Kelurahan Besar. This community service activity has been carried out through outreach activities and direct practice of making dish soap. This activity has been proven to increase participants' knowledge and provide positive experiences in producing products that are used daily, namely soap products. Participants are sure that they will be able to make similar soap products themselves, so it is hoped that they can save on spending on buying these products.